2015
DOI: 10.1007/s10858-014-9894-3
|View full text |Cite
|
Sign up to set email alerts
|

A minor conformation of a lanthanide tag on adenylate kinase characterized by paramagnetic relaxation dispersion NMR spectroscopy

Abstract: NMR relaxation dispersion techniques provide a powerful method to study protein dynamics by characterizing lowly populated conformations that are in dynamic exchange with the major state. Paramagnetic NMR is a versatile tool for investigating the structures and dynamics of proteins. These two techniques were combined here to measure accurate and precise pseudocontact shifts of a lowly populated conformation. This method delivers valuable long-range structural restraints for higher energy conformations of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Unfortunately, attempts to enhance relaxation dispersion effects by paramagnetic lanthanide tags have so far been thwarted by difficulties distinguishing motions of the protein from those of the tag [151,152,198]. Alternatively, however, chemical exchange saturation transfer (CEST) experiments can be used to measure chemical shifts and PCSs of lowpopulated states.…”
Section: Relaxation Dispersion and Cest Experiments On Protein Signalmentioning
confidence: 99%
“…Unfortunately, attempts to enhance relaxation dispersion effects by paramagnetic lanthanide tags have so far been thwarted by difficulties distinguishing motions of the protein from those of the tag [151,152,198]. Alternatively, however, chemical exchange saturation transfer (CEST) experiments can be used to measure chemical shifts and PCSs of lowpopulated states.…”
Section: Relaxation Dispersion and Cest Experiments On Protein Signalmentioning
confidence: 99%
“…Although the effective ''linkers'' between the protein-bound T1/T2 are the same as those of the CLaNP-5 and CLaNP-7 tags, the chiral elements of the T1/T2 design may help shed light on the source of the residual motions of the CLaNP-5 tag, recently reported in relaxation dispersion NMR experiments. 39 In conclusion, we have demonstrated that the enantiomeric T1/T2 tags, which can be readily synthesised in parallel, can provide long-range complementary structural information from the same tagging site, thus requiring fewer double-cysteine protein mutants for structural investigations. This reflects the fact that attachment of the tags produces a pair of diastereomeric protein-tag conjugates.…”
Section: And Table S4 (Esi †) the Pcss Of Each Enantiomer Bound To Th...mentioning
confidence: 81%
“…It has 29 been shown that combining relaxation dispersion with PCS data can potentially be very powerful but paramagnetic tag mobility is still a large problem, because it causes additional, undesired relaxation dispersion effects. 89,90 In conclusion, paramagnetic NMR has shown to have many applications for protein NMR and it is expected that its star will brighten in the future. PRE has been used widely, but the power of PCS and pRDC is still to be appreciated more by many in the NMR field.…”
Section: Conclusion and Perspectivementioning
confidence: 99%